The Influence of Justice and Organizational Culture on Commitment with the Mediation of Job Satisfaction among PT Grab Bali Employees - I Putu Revadio Pratama Putra; Agus Wahyudi Selasa Gama; Gde Bayu Surya Parwita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The advancement of an organization is strongly influenced by the strategic role of its workforce, which acts as a driving force behind institutional transformation. This research explores how perceptions of fairness in organizational practices and the internal cultural environment contribute to enhancing employee loyalty, with work-related satisfaction positioned as a bridging element in this dynamic. The investigation involved a complete enumeration of the 50 staff members employed at PT Grab Teknologi Bali, utilizing comprehensive survey methods including structured questionnaires, guided interviews, and document review. Analytical interpretation was conducted through the application of path modeling techniques. The empirical results reveal that equitable treatment within the organizational setting significantly fosters greater job satisfaction among employees. In parallel, the organizational ethos reflected in shared norms and values also plays a critical role in elevating employee contentment. Furthermore, both fairness in management practices and cultural alignment within the workplace have a direct and meaningful influence on the level of commitment displayed by employees. Job satisfaction, in turn, emerges as a key predictor of organizational allegiance. Finally, the analysis substantiates that job satisfaction effectively serves as a mediating pathway linking organizational fairness and culture to heightened employee commitment. These findings underscore the importance of fostering an environment where fairness and a strong organizational culture are prioritized, as they directly impact employee satisfaction and loyalty. Organizations that implement transparent and fair management practices, while also nurturing a cohesive cultural environment, create a foundation for long-term employee commitment. Additionally, the study emphasizes the need for organizations to continuously assess and improve their internal practices, not only to maintain fairness but also to align their cultural values with the expectations of their workforce. By doing so, companies can enhance job satisfaction, which ultimately drives higher levels of employee commitment and overall organizational success.